2024
DOI: 10.1172/jci.insight.175785
|View full text |Cite
|
Sign up to set email alerts
|

Adverse outcomes and an immunosuppressed endotype in septic patients with reduced IFN-γ ELISpot

Evan L. Barrios,
Monty B. Mazer,
Patrick W. McGonagill
et al.

Abstract: predictive metrics in critical illness and this technology (provisional patent application 63/521,817) is evaluated in this research. SCB, LLM, RSH, and the University of Florida may receive royalty income based on a technology developed by SCB and others and licensed by Washington University in St. Louis to IFDx LLC. That technology is evaluated in this research. CCC and the University of Cincinnati may receive royalty income based on a technology developed by CCC and others and licensed by Washington Univers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 60 publications
1
4
0
Order By: Relevance
“…Crucially, by normalizing IFNγ levels to cell counts, our method confirms the presence of both quantitative and qualitative lymphocyte defects. Our findings also align with recent literature, including works by Barrios et al ( 16 ), who have demonstrated the prognostic value of whole blood IFNγ levels using ELISpot assays ( 8 , 16 ). Unlike previous studies, however, our assay is both precise and semi-automated, providing results within 6 hours after a 4-hour ex vivo incubation period following sample collection.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Crucially, by normalizing IFNγ levels to cell counts, our method confirms the presence of both quantitative and qualitative lymphocyte defects. Our findings also align with recent literature, including works by Barrios et al ( 16 ), who have demonstrated the prognostic value of whole blood IFNγ levels using ELISpot assays ( 8 , 16 ). Unlike previous studies, however, our assay is both precise and semi-automated, providing results within 6 hours after a 4-hour ex vivo incubation period following sample collection.…”
Section: Discussionsupporting
confidence: 93%
“…Our assay builds on the foundational work of Hotchkiss et al ( 9 ), Barrios et al ( 16 ), and Venet et al ( 17 ) by incorporating IFNγ to evaluate immune functionality ( 26 , 27 ). Crucially, by normalizing IFNγ levels to cell counts, our method confirms the presence of both quantitative and qualitative lymphocyte defects.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Simultaneously, with advancing research into sepsis, a significant number of preclinical and clinical studies have observed that hosts often exhibit an excessive state of immunosuppression in the later stages of the disease. This severe immunoparalysis mediates secondary infections, subsequent deaths, or severe adverse prognoses ( 93 , 213 ). In this context, there has been a shift in focus from “immunosuppressive therapy” to “immune enhancement therapy” or “immune stimulation therapy” in an effort to reverse the state of immune paralysis in sepsis hosts.…”
Section: Clinical Studies Of Immunotherapy In the Treatment Of Sepsismentioning
confidence: 99%